Prospects and Dimensions of Conflict Resolution Programs in the Islamic Context (American Journal of Islam and Society, 2013)
Amr Abdalla (professor and vice rector, University for Peace, San Jose, CostaRica) visited the International Institute of Islamic Thought (IIIT) on February1, 2013, to discuss the challenges of conflict resolution and peace that hascaught the attention of so many Muslim and non-Muslim scholars and policymakersfor several decades. As the Muslim world remains plagued with violentconfrontations between states and non-state actors, regional and nationalsectarian conflicts, and domestic conflicts with gender and family elements,such a discussion is very timely.The outbreak of the Arab Spring, which has resulted in several Islamistgroups taking power, has raised various questions: Why is it important to talk about conflict resolution and peace building in an Islamic context? How canthe theoretical be combined with the practical? How does Islam fit into thedemonstrations that occurred during the Arab Spring as well as into modernity?This is, according to Abdalla, the first opportunity that contemporaryMuslims have had to answer these questions for themselves ...